Revitalizing Old Facades: Innovations in Facade System Installation and Preservation: Merevitalisasi Fasad Lama: Inovasi dalam Pemasangan dan Pelestarian Sistem Fasad - Ulugbek, Tojiboev; Marjona, Kamilova (Indonesian Journal of Innovation Studies, 2024)
This article presents a novel approach to enhancing the aesthetic appeal and longevity of old building facades through the installation of a new facade system. The study aims to improve the appearance of buildings while safeguarding the integrity of existing facades and mitigating various associated challenges. The methodology involves a detailed analysis of the old facade's condition, selection of appropriate materials and technologies for the new system, and implementation strategies for seamless integration. Results indicate significant improvements in building aesthetics, increased durability, and reduced maintenance costs. The implications of this research extend to urban planning, heritage preservation, and sustainable architectural practices, offering valuable insights for architects, engineers, and policymakers globally. Highlights: Facade renovation enhances building aesthetics and preserves historical architecture. Innovative materials and technologies ensure long-term sustainability and reduce maintenance costs. Global impact: Research findings inform urban development practices, emphasizing heritage preservation and sustainable building strategies. Keywords: Facade System, Building Renovation, Modernization